PENCEGAHAN DAN PENANGANAN BALITA STUNTING MELALUI PEMAHAMAN SERTA IMPLEMENTASI BUKU KESEHATAN IBU DAN ANAK (KIA) OLEH IBU BALITA DAN KADER DI DESA BANARAN, KABUPATEN NGANJUK, JAWA TIMUR - Irwanto Irwanto; Risky Vitria Prasetyo; Hanna Dyahferi Anomsari; Ayling Sanjaya; Egi Azhar Rafsanjani; Firyal Nadiah Rahmah (Jurnal Abdi Insani, 2023)
Stunting is still a problem around the world, particularly Indonesia where the prevalence of stunting in 2020 was 26.92%. The short-term impact of stunting included an increased risk of morbidity and mortality due to infectious diseases, while, long-term impacts of stunting can cause obesity, impaired cognitive function, and work productivity. One of the efforts to prevent stunting is the use of the Maternal and Child Health (MCH) Handbook by pregnant women and children aged under 5 years which has not been implemented properly. This community service activity aims to provide training in filling out the MCH handbook and educate the public on the importance of monitoring stunting in babies and children. Methods for implementing this activity include lecture in presentation form, discussion, and training approaches. A pre-test and post-test were carried out before and after this activity. A total of 80 participants took part in this activity, including the Head of Kertosono District, the Head of Banaran Village, the Head of the Kertosono Community Health Center and his staff, health cadres, and mothers who have stunted children, consisting of 37 Banaran's health cadres and mothers with stunted toddlers (72% of total stunted children in Banaran). It was found that there was an increase in participants' ability to fill out the MCH Handbook; before the activity, the mean pre-test score was 77.03 Â± 16.64 and the post-test score was 88.65 Â± 12.508. Training in understanding how to fill out the MCH Handbook to prevent stunting is very effective.